FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - nalurita, Shela; Lubis, Syarif Hidayah (SCIENTIA JOURNAL, 2020)
The purpose of this tscientific work is to analyze the effect of profitability, liquidity, and solvency on prices at manufacturing companies in the Indonesian stock exchange. There are several limitations of the problem in this study, first of the scope will only use the financial ratios of profitability or profitability using the Return On Asset ratio, Liquidity using the current ratio or Current Ratio, and Solvency using the ratio of Debt to Equity Ratio and the effect on Share Prices at Consumption Goods Industry Companies listed on the Indonesia Stock Exchange from 2015 to 2019. The analysis technique used is multiple linear regression, using the classic assumption test, t test, and f test. Hypothesis results obtained that Return On Assets have a positive influence on stock prices with a value of t count 4.406 and a significance of 0.000, while the Current Ratio has a negative effect on stock prices t count -0.259 with a significance of 0.796 and Debt to Equity Ratio has a negative effect on stock prices with a value of t count -1,141 with a significance of 0.257. The test results of the influence of Return On Assets, Current Ratio, and Debt to Equity Ratio have a positive and significant relationship to stock prices with a value of 27,266 and a significance of 0,000.